Preface - Kołodziejczyk, Hanna Zofia (Research Papers in Economics and Finance, 2017)
Dear Readers,I have the pleasure of presenting to you the second issue of our research journal entitled „Research Papers in Economics and Finance” (REF), published by the Faculty of Economics at Poznań University of Economics and Business. Caring about the highest level of the content of our publications, we publish only the manuscripts which have received two reviews under the “peer review” procedure, after initial verification done by the Editorial Committee. The articles published within REF are available online in English and in an open mode.REF is a quarterly journal, with the second issue containing six research articles. Two of the articles focus on the social and socio-economic aspects of development and business, one article looks at small family businesses and their path to growth; another paper dwells on the topic of sustainable agriculture, with two last research articles depicting financial subject matters such as currency rates and asset pricing. Yours faithfully,  dr Hanna Kołodziejczyk - Editorial Committee